Cover Picture: Solvent‐Adaptive Behavior of Oligospirobifluorenes at the Surface of Quartz Crystal Microbalances—A Conformational Process (ChemPlusChem 8/2017). Issue 8 (29th March 2017) - Pyka, Isabella; Lubczyk, Daniel; Saiju, Mandira D. S.; Salbeck, Josef; Waldvogel, Siegfried R.
Abstract : The cover picture shows the reversible change in the shape of a blowfish between its flat and inflated forms. This picture is a suitable metaphor for the reversible conformational change of an oligospirobifluorene derivative into an open structure in aromatic solvents. The flexible biaryl axis linking the spirobifluorene moieties is crucial to the conformation change, which arises from the strong attraction between the host and the solvent guest molecules. Details are given in the Communication by S. R. Waldvogel and co‐workers onpage 1116 in Issue 8, 2017 (DOI:10.1002/cplu.201600583 ).